Non-syndromic multiple odontogenic keratocyst finding with Cone-beam Computed Tomography (CBCT): A rare case report - Ichda Nabiela Amiria Asykarie; Farina Pramanik (Ikatan Radiologi Kedokteran Gigi Indonesia, 2023)
Objectives: The aim of this case report is to describe the radiograph pattern of non-syndromic multiple odontogenic keratocyst (OKC). The oral and maxillofacial region was frequently affected by the developmental odontogenic cyst known as OKC, which develops from the dental lamina or its remnants. The nevoid basal cell carcinoma syndrome (NBCCS) or the Gorlin-Goltz syndrome was typically associated with multiple OKC; however, in about 5% of patients, there were many cysts without a concurrent syndromic presentation. Case Report: A 38- year-old female came to the dental radiology installation of the Dental and Oral Hospital, Universitas Padjadjaran, who had been referred for a CBCT examination. She had a history with a dentist about 1 month ago, complaining of dislodged fillings on anterior mandible teeth and complaints of missing several posterior mandible teeth. The patient had a previous panoramic examination; multiple radiolucent lesions were found incidentally. She has no pain, and clinical features showed no evidence of swelling; then, the dentist recommended a CBCT examination with a suspect dental cyst on a posterior mandible dextra. Conclusion: Based on the examination results, it was concluded that the cone beam computed tomography examination showed the radiolucent lesion, well-defined with a scallop border; this case was radiodiagnosis as suspected non-syndromic multiple odontogenic keratocyst.